Vibration of a U-shaped steel–concrete composite hollow waffle floor under human-induced excitations. Issue 14 (October 2020) - Zhang, Xi; Li, Qing; Wang, Yousan; Wang, Qiming
The U-shaped steel–concrete composite hollow waffle floor is an innovative slender large-span floor system, where severe vibration may occur under human-induced excitations. In this research, a theoretical analysis and experimental testing are performed to explore the vibration behaviour of the composite hollow waffle floor. First, the natural frequency formula is proposed based on orthotropic thin plate theory, and the main rigidity calculation for the composite hollow waffle floor is given. Second, the mode shape, frequency and damping ratio of the composite hollow waffle floor are captured by on-site tests and validated by analytical and numerical methods, indicating that the floor has a low-frequency with a low damping ratio. Third, the vibration response of the composite hollow waffle floor is obtained by walking and running tests considering the influence of the frequency, spatial position, group size and route; in addition, the relationships between the values involved in the vibration evaluation are discussed. Finally, the composite hollow waffle floor presents satisfactory vibration performance evaluated by the threshold values among the current codes.